Interband Photoconductivity of Metamorphic InAs/InGaAs Quantum Dots in the 1.3–1.55-μm Window - Sergii Golovynskyi; Oleksandr I. Datsenko; Luca Seravalli; Giovanna Trevisi; Paola Frigeri; Ivan S. Babichuk; Iuliia Golovynska; Junle Qu (Nanoscale Research Letters, 2018)
Abstract Photoelectric properties of the metamorphic InAs/In x Ga1 − x As quantum dot (QD) nanostructures were studied at room temperature, employing photoconductivity (PC) and photoluminescence spectroscopies, electrical measurements, and theoretical modeling. Four samples with different stoichiometry of In x Ga1 − x As cladding layer have been grown: indium content x was 0.15, 0.24, 0.28, and 0.31. InAs/In0.15Ga0.85As QD structure was found to be photosensitive in the telecom range at 1.3 μm. As x increases, a redshift was observed for all the samples, the structure with x = 0.31 was found to be sensitive near 1.55 μm, i.e., at the third telecommunication window. Simultaneously, only a slight decrease in the QD PC was recorded for increasing x, thus confirming a good photoresponse comparable with the one of In0.15Ga0.75As structures and of GaAs-based QD nanostructures. Also, the PC reduction correlate with the similar reduction of photoluminescence intensity. By simulating theoretically the quantum energy system and carrier localization in QDs, we gained insight into the PC mechanism and were able to suggest reasons for the photocurrent reduction, by associating them with peculiar behavior of defects in such a type of structures. All this implies that metamorphic QDs with a high x are valid structures for optoelectronic infrared light-sensitive devices.